Performance Économique du Canada en 1984 : une Année Décevante - Landry, Jean-Luc (Assurances)

(untitled) (HEC Montréal, 1985)
1984 has been a difficult year for Canada but one cannot blame Canadian policy makers since the Canadian economy was unusually influenced by outside events. ln particular, the high level of interest rates in the United States and the strength of the U.S. dollar in foreign exchange markets imposed a major deflationary discipline on the Canadian economy. Nevertheless, Mr. Landry finds some positive development particularly with respect to inflation.